Beyond barriers: The role of preexposure prophylaxis in the prevention of human immunodeficiency virus in women - Alex Dang; Hillary Debs; Johnny Ruiz; Amber Vu; Melissa E Badowski (Journal of International Medical Research)
Preventive measures for human immunodeficiency virus infection have greatly evolved with the approval of preexposure prophylaxis. Despite their effectiveness, a significant gap exists in the initiation and adherence to these preventive measures among cisgender women. This review aims to highlight available implementation models to increase preexposure prophylaxis use and adherence in this population. A narrative review was conducted to identify studies focusing on preexposure prophylaxis use among cisgender women. Ultimately, 15 studies were included and categorized based on their intervention type: behavioral, health clinic, community, pharmacy, technology, or mobile. This review identified several intervention models that improved preexposure prophylaxis use and adherence among cisgender women. Behavioral interventions, such as preexposure prophylaxis-trained nurses and combined counseling with short message service reminders, significantly improved adherence. Health clinic-based interventions demonstrated the importance of regular follow-up and the potential for improved adherence through injectable preexposure prophylaxis. Community interventions highlighted the effectiveness of referral systems and technology-driven approaches, including mHealth interventions and real-time electronic adherence monitoring, to promote preexposure prophylaxis uptake and adherence. Implementing diverse interventions may considerably improve adherence and reduce the human immunodeficiency virus transmission rates in this population.